Serial Examination of Platelet Function Tests Might Predict Prognosis of Patients with Acute Ischemic Stroke—A Cohort Study - Hsin-Ju Ho; Li-Ching Wu; Yu-Wei Chen (Diagnostics)
Background: This study investigated whether point-of-care platelet function measurements could predict favorable outcomes in patients with acute ischemic stroke (AIS). Antiplatelet agents, such as aspirin, are known to reduce the risk of recurrent stroke by 20–30%. However, identifying nonresponders to therapy remains a clinical challenge. The study aimed to assess the prognostic value of serial Platelet Function Analyzer (PFA)-100 measurements and hematological ratios in AIS patients. Methods: A prospective cohort study was conducted on 212 AIS patients in Taiwan. Platelet function was assessed at baseline, week 2, and week 4 using PFA-100. The primary outcome was functional recovery, defined by a modified Rankin Scale (mRS) score of 0–3, at 1-month and 1-year. Subgroup analyses compared outcomes between pre- and post-aspirin administrations. Statistical analyses examined the association between changes in platelet function and clinical outcomes. Results: Difference in collagen and epinephrine (CEPI) measurements between baseline and week 2 was associated with favorable mRS scores (p < 0.001). A difference in CEPI closure time greater than 99 seconds was most predictive of a favorable outcome with an adjusted odds ratio of 11.859 (95% CI 2.318–60.669) at 1-month follow-up. Subgroup analyses revealed predictive value in pre-aspirin measurements at 1-month follow-up (p = 0.007). Conclusions: Serial PFA-100 measurements and hematological biomarkers, specifically changes in on-treatment CEPI closure times, may help predict favorable clinical outcome in AIS patients. These findings suggest that dynamic platelet function assessment could play a role in optimizing antiplatelet therapy in AIS management.